Glucosamine-magnesium composite as functional carriers: structural characteristic, controlled Mg2+ release and emulsion stability - Zhai, Yayuan; Chen, Yue; Gao, Ang; Dou, Yichen; Gao, Yang; Xie, Heran (Frontiers in Nutrition, 2025)
This study aimed to develop a glucosamine-magnesium composite (GlcN-Mg) as a novel Pickering emulsion stabilizer for the preparation of GlcN-Mg stabilized Pickering emulsion (GlcN-Mg PE) and systematically characterize its structural properties and emulsification performance. Structural analysis revealed that Mg2+ coordination reduced GlcN⋅HCl particle size from 1,117 ± 222.58 to 393.8 ± 45.42 nm, expanded its crystal lattice, and created a porous structure with a 22.9 ± 1.80 nm pore size. In vitro studies have shown that GlcN-Mg exhibits exceptional stability in food matrices and controlled Mg2+ release during gastrointestinal digestion. Then GlcN-Mg composite was employed to prepare water-in-oil (W/O) GlcN-Mg PE under different homogenization speeds (5,000–25,000 rpm), GlcN-Mg concentrations (0.3%–1.3%), and oil-to-water ratios (3:7–8:2). Rheological analysis indicated that GlcN-Mg PE exhibited a distinct threshold effect under varying conditions, while environmental factors significantly influenced emulsion stability. Furthermore, during in vitro gastrointestinal digestion, GlcN-Mg PE exhibited controlled-release ability, with the Mg2+ release rate reaching 80.42 ± 1.94% during intestinal digestion. Its stability across a wide range of conditions highlights its potential applications in complex emulsion systems.